Engineering writing by design creating formal documents of lasting value /cEdward J. Rothwell, Michael J. Cloud - Rothwell, Edward J.; Cloud, Michael J. (CRC Press, Taylor and Francis Group, 2014)
The purpose of the present book, however, is to speak to the engineering writer. Our basic premise is that engineering material should be written as deliberately and carefully as it will be read. Engineers are smart people and their work is important. Their writing should not be inaccurate, vague, ambiguous, or otherwise opaque. To a great extent, modern engineering is an extension of science and mathematics and is therefore amenable to clear and logical exposition. Some aspects of engineering remain more art than science, to be sure. We would argue, however, that in such cases it is especially important for engineers to write precisely, as readers will be in less of a position to close expository gaps through deductive reasoning